Recurrent ovarian torsion in a premenarchal girl - Lee, Yee Lin; Lee, York Tien; Chin, Xinyi; Sreedharan, Aravind Venkatesh; Vasanwala, Rashida Farhad (Science Repository, 2019)
A 10-year-old girl presented with a recurrence of left ovarian torsion where she presented with intermittent left sided abdominal pain for 2 days. She had a similar presentation occuring 1 month ago. The patient underwent successful ovarian salvage with laparoscopic left ovary detorsion and bilateral oophoropexy 5 hours after presentation. Tumour markers were not raised. Intraoperative incisional ovarian biopsy showed no evidence of malignancy. Ovarian torsion is a rare gynaecological emergency in children with nonspecific symptoms. Early recognition and surgery are important to prevent ovarian necrosis. The presentation of acute onset unilateral abdominal pain on the background of a similar previous presentation should alert the clinician of this diagnosis. Although ovarian torsions occur more commonly in the presence of adnexal masses more than 5cm in size, it can also occur in normal ovaries especially in the premenarchal age group. Laparoscopic detorsion is the treatment of choice with oophoropexy a feasible option for prevention of a recurrence. Close follow up with ovarian surveillance is required to ensure resolution of ovarian enlargement.